Implicações da terapia estrogênica associada ao exercício físico sobre a função cardíaca de ratas infartadas e ovariectomizadas - Simoes, Simone Alves de Almeida (2019)
There is an increase in the incidence of cardiovascular events such as myocardial infarction (MI) after menopause. However, the use of estrogen therapy (E2) remains controversial. The aim of this study was to evaluate the effects of E2, alone and combined with exercise training (ET), on cardiac function and remodeling in ovariectomized (OVX) rats after MI. Wistar female rats underwent ovariectomy, followed by MI induction were separated into five groups: S; MI; MI+ET; MI+E2; and MI+ET+E2. Fifteen days after MI or sham surgery, treadmill ET and/or estrogen therapy [17-β estradiol-3-benzoate (E2), s.c. three times/week] were initiated and maintained for 8 weeks. After the treatment and/or training period, the animals underwent cardiac hemodynamic evaluation through catheterization of the left ventricle (LV); the LV systolic and diastolic pressures (LVSP and LVEDP, respectively), maximum LV contraction and relaxation derivatives (dP/dt+ and dP/dt−), and isovolumic relaxation time (Tau) were assessed. Moreover, histological analyses of the heart (collagen and hypertrophy), cardiac oxidative stress [advanced oxidation protein products (AOPPs)], pro- and antioxidant protein expression by Western blotting and antioxidant enzyme activity in the heart were evaluated. The MI reduced the LVSP, dP/dt+and dP/dt−but increased the LVEDP and Tau. E2 did not prevent the MI-induced changes in cardiac function, even when combined with ET. An increase in the dP/dt+ was observed in the E2 group compared with the MI group. There were no changes in collagen deposition and myocyte hypertrophy caused by the treatments. The increases in AOPP, gp91-phox, and angiotensin II type 1 receptor expression induced by MI were not reduced by E2. There were no changes in the expression of catalase caused by MI or by the treatments, although, a reduction in superoxide dismutase (SOD) expression occurred in the groups subjected to E2 treatment. Whereas there were post-MI reductions in activities of SOD and catalase enzymes, only that of SOD was prevented by ET. Therefore, we conclude that E2 therapy does not prevent the MI induced changes in cardiac function and worsens parameters related to cardiac remodeling. Moreover, E2 reverses the positive effects of ET when used in combination, in OVX infarcted female rats.